A Review of Achieving Frequency Reconfiguration for Antennas in Wireless Communications - Hoang Thi Phuong Thao (Tạp chí Khoa học và Công nghệ, 2023)
Reconfigurable antennas are a type of smart antenna that is able to change whose properties, including resonant frequency, polarization, radiation pattern, and a combination of these properties. Reconfigurable antennas can switch between their configuration states to operate at different frequency bands for multiple standards, change their radiation patterns for direction finding, or change their polarization for polarization diversity. Therefore, they are a solution for modern wireless communications to meet the requirements of the system’s multi-functionality. This paper presents different reconfigurable antennas with various techniques to obtain antenna reconfiguration. The reconfigurable antenna can be achieved using electrical components (PIN diodes, RFMEMSs, varactors, FETs), optical diodes, smart materials (liquid crystal or ferrites), or physical alteration of antenna structures. The comparison and summarization of different reconfiguration techniques are described in the paper. The publications on reconfigurable antennas are mentioned and illustrated with discussions.